เซลล์บุผนังหลอดเลือดในโรคเบาหวาน: Vascular endothelium in diabetes mellitus - Malakul, Wachirawadee (Asian Health, Science and Technology Reports, 2011)
The endothelium plays a key role in the regulation of numerous vascular functions, including vascular tone, vascular inflammation, and coagulation. Dysfunction of the vascular endothelium is thought to be an early event in the beginning of atherosclerosis and important in the vascular complications in diabetes mellitus. There are many mechanisms that contribute to endothelial dysfunction in diabetes include the activation of protein kinase C (PKC) pathways, increased polyol pathway flux, accelerated non-enzymatic formation of advanced glycation end products (AGEs), and increased oxidant stress. Therefore, this article summarizes the important mechanisms of endothelial dysfunction in diabetes, which lead to the therapeutic application or drug development for the treatment or prevention of vascular complications that may occur in diabetic patients.